2022
DOI: 10.3389/fmed.2022.977620
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of insulin in treating severe hypertriglyceridaemia in the third trimester of pregnancy

Abstract: This study aims to investigate the efficacy of insulin in treating severe hypertriglyceridaemia (HTG) during the third trimester of pregnancy. Women with severe HTG (TG ≥ 11.30 mmol/L) in the third trimester of pregnancy who received clinical examination and delivered in Hubei Maternal and Child Health Hospital from 01 January 2017 to 30 September 2021 were recruited. Patients with TG ≥ 11.30 mmol/L at 30–32 weeks of gestation were treated with a low-fat diet and insulin as the insulin treatment group. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…[2,3] Some reported that 70% of APIP is caused by cholelithiasis, and about 4-30% of APIP is caused by hyperlipidemia. [2,4] At the same time, hyperlipidemia as the risk factor of severe APIP has been con rmed in many studies. [5,6] During gestation, with the uterus increases, the organ compensatory matrix upward or lateral displacement, the pancreas position relatively deep, physiological alterations in pain perception, clinical signs and symptoms are often not typical of APIP.…”
Section: Introductionmentioning
confidence: 95%
“…[2,3] Some reported that 70% of APIP is caused by cholelithiasis, and about 4-30% of APIP is caused by hyperlipidemia. [2,4] At the same time, hyperlipidemia as the risk factor of severe APIP has been con rmed in many studies. [5,6] During gestation, with the uterus increases, the organ compensatory matrix upward or lateral displacement, the pancreas position relatively deep, physiological alterations in pain perception, clinical signs and symptoms are often not typical of APIP.…”
Section: Introductionmentioning
confidence: 95%